2000
DOI: 10.3928/0022-0124-20001101-05
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Critical Thinking Disposition Inventory in Critical Care Orientation

Abstract: In the current health care environment it is imperative that orientation programs be effective and efficient in the preparation of nurses entering critical care nursing. Institutions strive to develop orientation programs that use the least amount of resources necessary to achieve the desired outcome. The desired outcome of the critical care orientation process is for nurses to use critical thinking skills to make sound clinical judgments based on scientific knowledge of critical care nursing. Identifying area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
1
21
2
Order By: Relevance
“…The reliability of the CCTDI has been measured in different populations such as graduate nurses, where the alpha values for the CCTDI total score are reported to be 0·87 (Smith‐Blair & Neighbors 2000) and lower than 0·80 (Profetto‐McGrath et al. 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The reliability of the CCTDI has been measured in different populations such as graduate nurses, where the alpha values for the CCTDI total score are reported to be 0·87 (Smith‐Blair & Neighbors 2000) and lower than 0·80 (Profetto‐McGrath et al. 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Colucciello (1999) reported that confidence was emerging as an important aspect of students' educational experiences and offered suggestions to build selfconfidence and reduce students' self-doubt. Smith-Blair and Neighbors (2000) suggested that nurses who are weak in systematicity may have problems with organization and prioritization of patient care, may make hasty, ineffective decisions, and are easily distracted. Ambivalence towards systematicity raises doubts about the quality of the decisionmaking process.…”
Section: Issues and Innovations In Nursing Educationmentioning
confidence: 99%
“…Critical thinking competence has thus been designated as an outcome for judging the quality of nursing programmes (Facione et al. 1994, Maynard 1996, Leppa 1997, Thorpe & Loo 2003) and for the development of clinical judgement (Facione & Facione 1997, Smith‐Blair & Neighbors 2000, Stone et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The CCTDI is designed to measure seven aspects of critical thinking: Truth‐seeking, Open‐mindedness, Analyticity, Systematicity, Self‐confidence, Inquisitiveness and Maturity (Facione 1990). The cross‐disciplinary conceptual definition in the Delphi report seems suitable for nursing research (Smith‐Blair & Neighbors 2000), although the use of the CCTDI in nursing is limited to date. Stone et al.…”
Section: Introductionmentioning
confidence: 99%